Modelling of Dynamic Pressure Conditions in District Heating Systems - Lindblom, Alexander (My University, 2015)
Water hammer is a problem that arises in district heating systems when there are abrupt changes in the flow operating conditions. As this often leads to damaged equipment it is of importance to simulate these effects in advance using various simulation tools. This thesis investigates how a general simulation software such as Dymola performs in comparison to the more specialized software available on the market for fluid transient calculations. The finite volume method in Dymola has been compared to the method of characteristics in the PFC simulation software. The overall conclusion is that Dymola may be used in cases where the system to be modelled is not too complex and accurate results are not required.
Keywords: Energiteknik; Energi; Energy Engineering; Energy